Detecting Patterns of Climate Change at Volcán Chimborazo, Ecuador, by Integrating Instrumental Data, Public Observations, and Glacier Change Analysis. Issue 4 (4th July 2017) - La Frenierre, Jeff; Mark, Bryan G.
Abstract : The people of Andean Ecuador face considerable risks due to climate change; however, a fundamental obstacle for those seeking to understand these risks is the lack of detailed, long-term meteorological data for the region. This research describes recent patterns of climate change at Volcán Chimborazo, Ecuador, through an integration of climatological data, qualitative data provided by local residents, and information derived from a detailed analysis of recent glacier change on the mountain. Although instrumental records indicate a local warming of 0.11°C decade −1 between 1986 and 2011 (0.26°C total), these data suggest that precipitation has remained largely unchanged. Local residents (farmers and nonfarmers, irrigators and nonirrigators), however, report that there has been a noticeable reduction in rainfall and surface water availability in recent decades, and the near ubiquity of this observation suggests that the instrumental record has not captured these patterns of climate change. Between 1986 and 2013, Chimborazo experienced a 21 percent (±9 percent) reduction in ice surface area and a 180 m increase in the mean minimum elevation of non-debris-covered ice. Because measured warming can only account for an ∼50 m increase in freezing level height, these changes indicate that shifting precipitation patterns are indeed occurring. These results show that integrating information from a variety of empirical and nonempirical sources provides valuable information about local manifestations of climate change that might otherwise remain unrecognized in highly heterogeneous mountain landscapes. This integrative capacity is a unique—and critically important—contribution that geographers can make to climate change science.